Analisis Retorika Pidato Prabowo Subianto Pada Pelantikan Presiden Tahun 2024-2029 (Kajian Teori Retorika Aristoteles) - Dama, Yunus; Monoarfa, Frediyanto; Arjoyo, Rahmatia; Djalilu, Yusrin; Abdullah, Fendra Amellia; Hino, Karmila; Mokoagow, Syakil (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
The purpose of this research is to describe Prabowo Subinato’s rhetoric in his 2024-2029 Presidential inauguration speech. The theory used to analyze is based on Aristotle’s Rhetoric theory which includes ethos, logos, and pathos. The method used in this research is qualitative description, by describing sentences that indicate the presence of ethos, logos, and pathos in Prabowo Subianto’s speech. The data source is a video of Prabowo Subianto’s presidential speech accessed through YouTube. The results showed that Prabowo Subianto’s speech reflected the application of Aristotle’s rhetorical theory through three main elements: ethos, logos, and pathos. In the ethos aspect, he emphasized the importance of integrity, morality, and leadership commitment to realize a clean and democratic government, reflecting the credibility and good character of the speaker. In terms of logos, Prabowo delivered rational arguments that invited the audience to think critically about the responsibility of leaders and the importance of collective efforts to overcome major problems such as poverty, showing rationality and structured logic. The pathos aspect is seen in the way he evokes the audience’s emotions, such as pride in Indonesia’s democracy and courage to face challenges, delivered through passionate and motivational words. By combining these three elements in a balanced way, Prabowo managed to establish credibility, provide strong arguments, and create a deep emotional connection with the audience, making his speech effective and inspiring.